Early stages of trachea healing process: (immuno/lectin) histochemical monitoring of selected markers and adhesion/growth-regulatory endogenous lectins - Grendel, T; Sokolský, J; Vaščáková, A; Hudák, V; Chovanec, M; Sabol, F; André, S; Kaltner, H; Gabius, H-J; Frankovičová, M; Lenčeš, P; Betka, J; et al. (Folia biologica, 2012)
Tracheotomy may be associated with numerous acute and chronic complications including extensive formation of granulation tissue. The emerging functional versatility of the adhesion/growth-regulatory galectins prompted us to perform a histochemical study of wound healing using rat trachea as model. By using non-cross-reactive antibodies and the labelled tissue lectins we addressed the issue of the presence and regulation of galectin reactivity during trachea wound healing. Beside localization of high-molecular-weight keratin, wide-spectrum cytokeratin, keratins 10 and 14, α-smooth muscle actin, vimentin, fibronectin, and Sox-2, galectins -1, -2, and -3 and their reactivity profiles were measured in frozen sections of wounded and control trachea specimens 7, 14, and 28 days after trauma. A clear trend for decreased galectin-1 presence and increased reactivity for galectin-1 was revealed from day 7 to day 28. Sox-2-positive cells were present after seven days and found in the wound bed. Interestingly, several similarities were observed in comparison to skin wound healing including regulation of galectin-1 parameters.
Keywords: galektiny; Wound Healing; Rats; Cell Adhesion; trachea; histocytochemie; tracheostomie; potkani Sprague-Dawley; Disease Models, Animal; mužské pohlaví; Tracheostomy; Galectins; Histocytochemistry; hojení ran; krysa rodu Rattus; modely nemocí na zvířatech; lektiny; zvířata; Humans; Lectins; biologické markery; Skin; Rats, Sprague-Dawley; tracheotomie; buněčná adheze; Biomarkers; Trachea; Tracheotomy; kůže; lidé; Male; Animals